2022
DOI: 10.3389/fimmu.2022.876195
|View full text |Cite
|
Sign up to set email alerts
|

Lactate: A regulator of immune microenvironment and a clinical prognosis indicator in colorectal cancer

Abstract: Lactate can play an immunosuppressive role in the tumor microenvironment and promote tumor development by recruiting and inducing the activity of immunosuppressive cells and molecules. High lactate concentrations are important for tumor cell metastasis, angiogenesis, and treatment resistance. With the in-depth studies on tumor metabolism, lactate, one of the key factors involved in glycolysis, has been increasing emerged its characteristic clinical value in colorectal cancer (CRC). In this study, lactate genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Finally, high lactate concentrations are important for tumor cell metastasis, angiogenesis, and treatment resistance. Of note, the lactate score has been recently shown as an independent prognostic factor for cancer that can be used as a clinical guide for predicting CRC progression and as an evaluation factor for immunotherapy effectiveness [60] . Interestingly, we also observed a positive correlation of Bifidobacterium with lactate, which further corroborates the predicted metagenomic pathway analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, high lactate concentrations are important for tumor cell metastasis, angiogenesis, and treatment resistance. Of note, the lactate score has been recently shown as an independent prognostic factor for cancer that can be used as a clinical guide for predicting CRC progression and as an evaluation factor for immunotherapy effectiveness [60] . Interestingly, we also observed a positive correlation of Bifidobacterium with lactate, which further corroborates the predicted metagenomic pathway analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has demonstrated that elevated lactic acid produced by Warburg effect is a poor prognostic indicator for metastatic lung cancer 9 . The effect of lactate has also been established and confirmed in the prognosis of colorectal cancer, 10 lung adenocarcinoma, 11 and esophageal squamous cell carcinoma 12 . Moreover, recent research has demonstrated that Warburg effect‐related genes have a significant effect on tumor progression and prognosis.…”
Section: Introductionmentioning
confidence: 94%
“…Another metabolite, lactate, can serve an immunosuppressive effect in the TME and promote tumor formation by attracting and stimulating the function of immunosuppressive molecules and cells [ 169 ]. It has been found to boost angiogenesis and provide oxygen and glucose to cancer cells, which in turn facilitates the growth, invasion, and migration of colon cells [ 169 ].…”
Section: Obesity-associated Alterations In the Gut Microbiome That Ma...mentioning
confidence: 99%
“…Another metabolite, lactate, can serve an immunosuppressive effect in the TME and promote tumor formation by attracting and stimulating the function of immunosuppressive molecules and cells [ 169 ]. It has been found to boost angiogenesis and provide oxygen and glucose to cancer cells, which in turn facilitates the growth, invasion, and migration of colon cells [ 169 ]. The lactate metabolized by cancerous cells exacerbates CRC progression by prompting macrophages to exhibit M2-type polarization and the production of high-mobility group box 1 (HMGB1), which is essential in maintaining nucleosome structure and controlling the transcription of many genes [ 170 ].…”
Section: Obesity-associated Alterations In the Gut Microbiome That Ma...mentioning
confidence: 99%